PENGARUH PERSEPSI SISWA TENTANG GAYA MENGAJAR GURU, MINAT BELAJAR, GAYA BELAJAR, DUKUNGAN SOSIAL DAN LINGKUNGAN KELUARGA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI MAN 6 PASAMAN BARAT - Lia Rahmi; Stevani; Rika Verawati (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine the influence of students' perceptions of teacher teaching styles, learning interests, learning styles, social support, and family environment on student achievement in economics at MAN 6 West Pasaman. This study uses an associative approach. The population was grades 10 and 11 students in economics at MAN 6 West Pasaman. The sampling technique used was total sampling. The results of this study indicate a significant influence between student perceptions of teacher teaching styles, learning interests, learning styles, social support, and family environment on student achievement, with an F-value of 19.268 > F-table 2.32 and a significance value of 0.000 <0.05.